The Effect of β-Alanine Supplementation on the Heat Shock Protein, Inflammatory and Neurotrophin Response in Animals Exposed to an Acute Heat Stress. (29th May 2020) - Hoffman, Jay; Belety, Tal; Horowitz, Michal; Epstein, Yoram; Bruchim, Yaron; Cohen, Hagit
Abstract: Objectives: The effect of 30-days of β-alanine (BA) supplementation on heat shock protein 70 (HSP70), inflammatory and neurotrophin responses in the hippocampus and hypothalamus of rats exposed to an acute heat stress was investigated. Methods: Animals were randomized to either a control (CTL) group or BA supplementation (100mg·kg −1 ) group. All animal were fed a normal diet and only differed regarding supplementation. Following supplementation animals were either exposed to the heat stress (120 min at 40–41°C) or were unexposed. Following the acute heat stress, or at the end of the supplementation period, animals were harvested and their brains removed. Immunohistochemical technique was used to detect expression of HSP70, brain-derived neurotrophic factor (BDNF), cyclooxygenase-2 (COX2) and neuropeptide Y (NPY) in the hippocampus subregions and paraventricular nuclear (PVN) region of the hypothalamus. Results: Three animals in CTL and one in BA did not survive the heat stress. Significant attenuation ( P 's < 0.005) in BDNF expression was noted in animals exposed to the heat stress compared to unexposed in all subregions (CA1, CA3 and DG) of the hippocampus and PVN. A significant elevation in BDNF expression in the CA3 subregion of rats fed BA and exposed to the heat stress was observed compared to exposed CTL animals. Significant elevations in COX2 was also noted in the CA1 and CA3 subregions in exposed compared to unexposed animals. COX2 expression was significantly greater ( P  ≤ 0.0065) in CTL compared with BA during heat exposure in the CA1 subregion of the hippocampus. Animals supplemented with BA also realized significantly higher HSP70 expression ( P  = 0.02) in the CA3 subregion of the hippocampus compared to CTL. Significant differences ( P 's < 0.05) in NPY expression in all subregions of the hippocampus and PVN were noted between exposed and unexposed animals. However, NPY expression was significantly higher ( P  ≤ 0.03) for BA compared to CTL in exposed animals in the PVN. Conclusions: Results suggested that BA supplementation appeared to increase resiliency to an acute heat stress and reduced the inflammatory response, while increasing HSP70 and neurotrophins expression. Funding Sources: Natural Alternatives International Inc., Carlsbad, CA, USA.